Historical study in phonetics - Al-Zahrani, Saied (Arab Journal for Sciences and Research Publishing, 2017)
In the name of Allah, the Most Gracious the Most Merciful, and the prayer on his noblemessenger, and on his family and companions and followers to the Day of Judgment. this researchhighlights the attention of the owners of each language sounds since ancient times, and perhaps one ofthe most important reasons that invited the Arabs, especially, to study them, it is our language thephonetics wasn’t known as this name for Arab until a late stage, Therefore, it did not go away from theworks of the advanced Arab scholars in the towards them and their disbursement and communication andpresentations and literary encyclopedias with their different arts. And other works such as medicine,wisdom and music, especially the work of sounds and melody, reading and recitation intensively, all thesesciences touch the sound of the side can be mixed these different sciences in the sound so as not to fall ona book is devoid of words in the science of sounds or effects. Therefore, we will follow the nations thatdealt with the science of sounds in our research by investigating and knowing the roles played by eachnation separately, hoping to reach in this research to the integration of the role of each nation in thescience of sound for the treatment of speech disorders or to adjust some similar letters that may bedifficult for many languages learners. However, these studies in Arabic or other languages were not inisolation from that progress in science in general. Therefore, there was a coefficient of language thattaught phonetics and dealt with the deficiencies of those who needed it. The study of all the nations thatdealt with the sounds and their development was not successive and sequentially intertwined. Theobservation of the evolution of this science in its various aspects was not sudden, but it was varied andvaried in each nation according to the interest of its people in that science and its care.
Keywords: Phonetics